MANAJEMEN MUTU LAYANAN PENDIDIKAN DI SMPN 10 MESUJI KECAMATAN PANCA JAYA MESUJI - Ahmad Lison Deser (UNISAN JURNAL, 2024)
In light of the foundation of the issues depicted over, the exploration centers around the nature of training administrations in view of value norms of schooling administrations at SMPN 10 Mesuji Kecamatan Panca Jaya Mesuji with a sub center around 5 components of administration quality at SMPN 10 Mesuji Kecamatan Panca Jaya Mesuji which comprises of; Nature of schooling administrations in the effects perspective Nature of instructive administrations in the part of sympathy (compassion) Nature of instruction administrations in the part of Dependability Nature of instruction administrations in the part of Responsiveness. The consequences of this study are proposed to be utilized as a wellspring of reference and extra data for future specialists, in regards to support quality to consumer loyalty. In additional examination, different factors outside the 5 aspects can be added or in any event, involving different elements of administration quality as autonomous factors. The improvement of the universe of training today has brought the universe of schooling, particularly in senior secondary schools, to encounter extremely close rivalry, secondary schools as organizations giving conventional schooling are one of the help enterprises.